5
$\begingroup$

How does one evaluate

$ \displaystyle\prod\limits_{n=1}^{\infty} \cos(\frac{y}{2^n}) $?

Seems fairly straightforward, as I just plugged in some initial values $n = 1, 2, 3,\dotsc$

$n = 1$

$ \sin(y)= 2\sin(\frac{y}{2})\cos(\frac{y}{2})$

$ \cos(\frac{y}{2}) = \sin(y)/2\sin(\frac{y}{2}) $

$n = 2$

$\sin(\frac{y}{2})= 2\sin(\frac{y}{4})\cos(\frac{y}{4}) $

$\cos(\frac{y}{4}) = \sin(\frac{y}{2})/2\sin(\frac{y}{4}) $

Hence,

$ \prod\limits_{n=1}^{\infty} \cos(\frac{y}{2^n}) = \sin(y)/2\sin(\frac{y}{2}) \times \sin(\frac{y}{2})/2\sin(\frac{y}{4}) ... \times \sin(\frac{y}{2^{n-1}})/2\sin(\frac{y}{2^n}) $

Then some denominators/numerators cancel, reducing the expression into

$ \prod\limits_{n=1}^{\infty} \cos(\frac{y}{2^n}) = \sin(y)/2^n\sin(\frac{y}{2^n})$

Is this expression no longer reducible?

Because apparently, somehow, the denominator seems to reduce to $y$

How does that work?

$\endgroup$
3
  • $\begingroup$ Read this mathworld.wolfram.com/SincFunction.html $\endgroup$ – Aditya Agarwal Jul 16 '15 at 11:26
  • $\begingroup$ In such questions usually need to find $\lim _{ n\rightarrow \infty }{ \prod _{ i=1 }^{ n }{ \cos { \left( \frac { x }{ 2^{ i } } \right) } } } $ which equal to $\frac { \sin { x } }{ x } $ by your method $\endgroup$ – haqnatural Jul 16 '15 at 11:30
  • $\begingroup$ As $c \to \infty$, $c\sin(\frac{x}{c}) \to x$ (use L'Hospital's rule, or interpret this as a derivative by letting $u=\frac{1}{c}$, so the denominator does reduce as you say. Nice work doing the rest by the way :) $\endgroup$ – ShakesBeer Jul 16 '15 at 11:32
7
$\begingroup$

Let's take a look at the finite product first:

$$\prod_{i=0}^k \cos\frac{x}{2^i} = \frac1{2^k}\frac{\sin 2 x}{\sin \frac{x}{2^k}}$$

which is the standard trick of multiplying the product by $\sin \frac{x}{2^k}$.

Now take limit as $k \rightarrow +\infty$ and you get:

$$\prod_{i=0}^\infty \cos\frac{x}{2^i} = \frac{\sin{2 x}}{x}$$

$\endgroup$
2
$\begingroup$

Hint: Use the Taylor series and let $n\rightarrow \infty:$ $$2^n\sin\left(\frac{y}{2^n}\right)= 2^n\left(\frac{y}{2^n}-\left(\frac{y}{2^n}\right)^3/3! + \dots\right) = y - \frac{y^3}{3!2^{2n}} + \dots$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.